Pengaruh Total Asset Turnover dan Current Ratio terhadap Return On Asset pada Perusahaan Sub Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Dini Fitriani; Berliana Fitri Febriyanti (Journal on Education, 2023)
Profitability is able to reveal the company's capacity to benefit from the assets used, the company's performance can be assessed as good if the company is able to use its assets efficiently and generate profits from all its assets. This study aims to determine whether Total Asset Turnover, Current Ratio has a significant effect on Return On Assets. In this study, the authors use Total Asset Turnover and Current Ratio as independent variables and Return on Assets as the dependent variable. The method used is statistical method and processed using SPSS 26. The population in this study were 28 transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study used a purposive sampling method. Based on these criteria, 24 companies can be obtained and there are 72 financial statements that will be used as data in this study. Based on the results of multiple linear regression analysis, the coefficient of determination is 24.0% and the influencing factor is Total Asset Turnover seen from the t-test calculation. The calculated t value for the Total Asset Turnover variable is 3,380, the t calculated for the Current Ratio variable is 2,006 and the calculated F value is 9,305 with a significant value of 0.000 <0.05